On the rate of convergence of weak Euler approximation for nondegenerate SDEs driven by Lévy processes - Zhang, Changyong; Mikulevičius, R. (2011)
The paper studies the rate of convergence of the weak Euler approximation for solutions to SDEs driven by Lévy processes, with Hölder-continuous coefficients. It investigates the dependence of the rate on the regularity of coefficients and driving processes. The equation considered has a nondegenerate main part driven by a spherically symmetric stable process.